Riparian Vegetation Structure of the Jengok River, Kutaliman, Kedungabanteng District, Banyumas Regency - Fikriyya, Nabela; Putri, Adinda Kurnia; Silalahi, Marina (MAIYAH, 2023)
Jengok River has a high value for the Kutaliman community. The community utilizes the ecosystem services of the Jengok River and is inseparable from the presence of riparian vegetation, which controls water quality. This study aimed to determine riparian vegetation structure on the Jengok River, Kutaliman, Kedungbanteng district, and Banyumas Regency. The research was conducted in October-November 2022 in the Jengok riparian zone using a quadrat transect with sizes 20x20 m2 for trees dan 2x2 m2 for understoreys. Data were analyzed using the Shannon-Wiener Diversity Index (H'), the Modified Hill's Ratio Evenness Index (e'), the Margalef Richness Index (DMg), and the Important Value Index (IVI). The results show that the diversity of riparian vegetation based on the Shannon-Wiener Diversity Index (H') is a moderate category, and the Evenness Index (e') is the distribution of individuals per species evenly. Furthermore, the Margalef Richness Index (DMg) shows 4.51 for trees and 4.34 for understorey. The highest IVI in the tree stratum was Lansium domesticum Corrêa. In contrast, in the understorey stratum was Musa paradisiacal L. This indicates both species have an essential role in their community